Copper mining bacteria: Converting toxic copper ions into a stable single-atom copper - Gracioso, Louise Hase (Sci Adv, 2021)
The chemical synthesis of monoatomic metallic copper is unfavorable and requires inert or reductive conditions and the use of toxic reagents. Here, we report the environmental extraction and conversion of CuSO(4) ions into single-atom zero-valent copper (Cu(0)) by a copper-resistant bacterium isolated from a copper mine in Brazil. Furthermore, the biosynthetic mechanism of Cu(0) production is proposed via proteomics analysis. This microbial conversion is carried out naturally under aerobic conditions eliminating toxic solvents. One of the most advanced commercially available transmission electron microscopy systems on the market (NeoArm) was used to demonstrate the abundant intracellular synthesis of single-atom zero-valent copper by this bacterium. This finding shows that microbes in acid mine drainages can naturally extract metal ions, such as copper, and transform them into a valuable commodity.